The influence of ceramic thickness on the mechanical properties of dual resin cements: literature review (Research, Society and Development, 2022)
The objective of this study is to clarify the extent to which the thickness of the ceramics influences the light curing and thus affects the mechanical properties of dual cure resin cements, through a literature review. Articles published in online databases were searched in which they evaluated whether there is an influence of ceramic thickness on the mechanical properties of dual cure resin cements. The databases used were PubMed, LILACS and SCOPUS. The research conducted by two authors was carried out in June 2022 and obtained the final result of 6 articles selected for the review. In this research, the authors report that dual cure resin cements can be used in zirconia crowns up to 2 mm, while for monolithic lithium disilicate crowns they can be used in pieces up to 2.5 mm. After reviewing the literature on the influence of ceramic thickness on the mechanical properties of dual cure resin cements, we can consider that in pieces from 2 mm there is a decrease in mechanical properties, including microhardness and degree of conversion.